Holocene sedimentation and sea level rise in the Sado Estuary, Portugal - Psuty, Norbert P. (2019)
The general geomorphologic developmental history of the Sado estuary is tied to the history of sea-level rise during the middle and late Holocene and to the history of sediment transport both downstream by the fluvial drainage system and alongshore by the northerly coastal drift. Several deep cores in the Sado estuary show an encroachment of Holocene sediments upward and inland across the Pleistocene surface. Although the trend line depicts a persistent sea-level-rise rate of about 1.7 mm/yr., this is an average and there is stratigraphic evidence for variation as interpreted from the sediment facies in the cores. Similar to other areas, the sediment history is one of transgression and some vertical accumulation during the rising phase, whereas horizontal accretion was delayed until after a reduction in the rate of rise about 2600 BP, when the fringing marsh began to develop and expand into the estuary. Abundant quantities of sand were brought into the southern portion of the estuary by alongshore drifting and barrier spit development. It is likely that major spit elongation and dune development coincided with the initiation of a lower rate of sea level rise and that both the spit and the estuary had contemporaneous positive budgets. An increased rate of sea-level rise in the past several centuries plus many centuries of human interference with sediment transport is responsible for the re-initiation of wetland attenuation through modern-day erosion and destruction of the margins of the high marsh.